Buckling Analysis of Composite Grid-Stiffened Cylindrical Shells Using a Generalized Equivalent Single Layer Theory - Hamid Mohammad Panahiha; Ali Davar; Jafar Eskandari Jam; Mohsen Heydari Beni; Majid Eskandari Shahraki (Mechanics of Advanced Composite Structures)
In this study, the buckling analysis of multilayer composite closed cylindrical shells, as well as composite grid cylindrical shells, was investigated using a high-order theory modified from Reddy’s third-order shear theory under simply supported conditions. The advantage of the present theory compared to other high-order theories is the calculation of the effect of the term of the shell section trapezoidal coefficient on relations related to displacement and strain fields, which improves the accuracy of the results. In grid shells, the discontinuous distribution of stiffness and mass of the shell between the reinforcing ribs and the distance between them is expressed by a suitable distribution function. In the case of integrated and grid cylindrical shells, the validation of the results was performed in comparison with other studies, as well as with the results of the numerical solution obtained using Abaqus software. It is shown that for the first buckling mode, the critical load first increases and then reaches a constant value and for the second buckling mode, the critical load first decreases and then reaches a constant value. Also, in the case of grid shells, by increasing the ratio of the cavity dimension to the dimensions of the whole shell, whether in single-cavity or multi-cavity mode, the present theory and finite element solution find more difference, indicating the higher accuracy of the present theory for integrated shells.